(untitled) (Scientia Agricola, 2010)
The term 'organically grown food' denotes products that have been produced in accordance with the principles and practices of organic agriculture. The use of alternatives to synthetic fertilizers is an important issue in organic systems. A two-year field experiment to evaluate effects of organic fertilizers on the yield and quality of open field grown tomatoes (Lycopersicon esculentum Mill.) was carried out in Southern Turkey in 2000 and 2001. Combinations of manure, blood flour and micronutrient preparations were used for fertilization, and conventional mineral fertilization was included as the control. Yield did not differ between the fertilization and the Conventional treatments in the first year of the study, but the highest yield was obtained from conventional in the second year. No differences were found between treatments in terms of fruit soluble sugar content or citric acid. The application of organic fertilizers positively affected the micronutritional element content of tomato fruits compared to the conventional treatment. Organic fertilization results in improved yield and fruit quality compared to conventional fertilization. In addition, organic fertilization should be supported in order to facilitate reuse and disposal of organic wastes and to maintain and/or increase soil fertility.